Genetic diversity and productivity of Gracilaria coronopifolia as alternative for food resource based on RAPD marker - Gut Windarsih; DWINITA WIKAN UTAMI; SITI YURIYAH (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Windarsih G, Utami DW, Yuriyah S. 2019. Genetic diversity and productivity of Gracilaria coronopifolia as alternative for food resource based on RAPD marker. Biodiversitas 20: 3758-3765. Gracilaria coronopifolia is one of potential seaweed as an alternative for food resources, especially for agar source. The information about the genetic profile of G. coronopifolia will be useful for assisting in conservation and breeding efforts. RAPD marker is expected to be utilized for characterization of the species with high productivity based on genetic profile. This research aims to determine the genetic diversity and productivity of G. coronopifolia based on RAPD marker. The samples were collected from Anyer Beach, Banten, Indonesia i.e. Tanjung Tum Beach, Mambruk Hotel Beach, and Patra Comfort Anyer Beach, as well as the cultivation ponds of seaweed in Lontar Village, Banten, Indonesia. Five RAPD primers (OPA-01, OPA-16, OPT-05, OPR-02, and UBC-594) were screened to characterize the genetic profile of samples. The results showed that all primers produced polymorphic bands. Based on the genetic profile, the samples of G. coronopifolia were separated into two main clusters, consisted of group A (Tanjung Tum Beach, Patra Beach, and Mambruk Beach) with a coefficient of similarity of 0.44 and group B (Lontar Village) with a similarity coefficient of 0.43. The sample from Lontar Village was separated outside from the other three samples at the waters of Anyer Beach. The sample from Lontar Village had the highest talus height (18.0 cm) and dry weight (1.250 g/clump). The UBC-594 primer was the most associated with the talus height and dry weight on the band size of 50 bp, thus this primer was assumed can be used as a selection marker for the talus height and dry weight of G. coronopifolia.